Genetic Architecture of Gum Content in Cluster Bean under Different Environments - Jhorar, B S; Solanki, K R; Jatasara, D S (Annals of Arid Zone, 2016)
Genectic architecture of gum content in cluster bean has been investigated using numerical and graphical analysis of a six-parent diallel cross under different environmental conditions. Environments exerted substantial effect on gene expression. The character was governed mostly by non-additive gene effects. The additive genetic component was stable whereas the dominance component significantly interacted with environments and was, thus, unstable. The mean degree of dominance invariably revealed overdominance in all the environments. Symmetry of positive and negative genes was observed in the parental population. One to four dominant genes governed inheritance of the gum content. Heritability estimates were low in all the environments. Graphical analysis revealed tharcultivars HG 182, FS 277 and DPS possessed the maximum number of dominant genes and hence their exploitation in breeding programmes for developing varieties with high gum content has been suggested.